The association between negative attributional style and working memory performance - Saylik, R.; Szameitat, A.J. (Bentham Science Publishers B.V., 2018)
Introduction: It has been proposed that negative attributions contribute to impairment in cognitive task processing. However, it is still unknown whether negative attributions influence task processing in all cognitive tasks. Methods: To investigate this, 91 healthy participants completed attributional style questionnaire and performed three Working Memory (WM) tasks, which associated with different functions of WM (i.e. Central Executive System (CES) and visuospatial sketchpad). Results: The results demonstrated that negative attributions contribute to the impairment in cognitive tasks which is associated with spatial working memory rather than main central executive functions (i.e. switching and inhibition). Conclusions: It is concluded that negative attributions may selectively disrupt spatial working memory functions, thus a detrimental effect of negative attributions may be task specific. © 2018 Saylik and Szameitat.
Keywords: Cambridge neuropsychological test battery; Central executive system; Individual differences; Negative attributional style; Spatial working memory; Working memory tasks